Evolution of advertisement calls in an island radiation of African reed frogs. (15th November 2017) - Gilbert, Cassandra M; Bell, Rayna C
Abstract: Differences in mating signals among incipient species are an important mechanism driving reproductive isolation and speciation. Here, we investigate male advertisement call divergence across a radiation of reed frogs from the Gulf of Guinea archipelago and the most closely related species on the African continent ( Hyperolius olivaceus ). The two species endemic to the island of São Tomé ( Hyperolius molleri and Hyperolius thomensis ) differ in body size, coloration and breeding ecology, yet they hybridize where their habitats overlap. A third species, Hyperolius drewesi, is sister to H. molleri and endemic to Príncipe Island. We found significant differences in average dominant frequency and average number of pulses per call among the four species. The strong relationship between body size and dominant frequency irrespective of geographical history, breeding habitat or acoustic environment suggests that differences in this component of the mating signal may be a by-product of adaptive changes in body size among the four species. Hybrid males are intermediate in size between H. molleri and H. thomensis and produce calls at intermediate dominant frequencies. Future efforts to characterize courtship behaviour and breeding habitat preference in allopatric and sympatric populations will provide additional insights as to the potential for reinforcement in this system.